IMPROVING PURCHASING DECISIONS THROUGH PRICE PERCEPTION AND PRODUCT QUALITY: THE MEDIATING ROLE OF BRAND IMAGE IN BOTANICA APARTMENT - Wijayanti, Allin; MH Nainggolan, Bonifasius (Journal of Management and Leadership, 2023)
This research examines the impact of brand impression through the mediators of pricing perception and product quality on a buying decision for a Botanical Apartment. This study used primary data from questionnaires with a purposive sampling technique and the PLS-SEM (Partial Least Squares - Structural Equation Modelling) method to investigate the stated hypothesis. Two sessions were used to complete the PLS-SEM analysis in two phases. The reliability and validity analysis is the first stage, and the estimate and validation of the path coefficients and the robustness of the structural models are the second and third stages, respectively. For statistical analysis, using a sample of 220 respondents was taken from residents living in The Botanica Apartment and applying Smartpls V.3.2.9 to test the hypothesis of the influence of variables simultaneously and partially. Research findings show that brand image influences purchasing decisions, product quality affects the brand image, product quality affects purchasing decisions, price perception affects the brand image, and price affects purchasing decisions. In addition, the study revealed that product quality impacts brand image indirectly through purchasing decisions, and price perception impacts brand image indirectly through buying decisions.